Assessment of infectious prevalence and sensitivity to antimicrobials in dog external otitis in Mineiros City Mid-West Region of Brazil (Research, Society and Development, 2022)
Otitis externa is an inflammatory disease very common in small animals, being one of the main affections that motivate dog and cat owners to seek veterinary care. It is a disease that has several triggering factors and infectious agents as the main causes. The clinical signs observed in animals are erythema, pain, itching, ear secretion, foul odor and shaking of the head. Diagnosis is based on anamnesis, clinical examination of the animal, with the aid of an otoscope, considering epidemiological findings, results of cytological examinations, cultures and antimicrobial sensitivity tests. Treatment is based on prior cleaning of the auditory canal combined with topical and/or systemic antimicrobial therapy. The objective of this work is to establish the bacterial, fungal and parasitic microbiota present in external infectious otitis of dogs and cats treated veterinary clinic, as well as to identify the most effective antimicrobials in vitro and obtain epidemiological data such as race, sex and predominant age group on this condition in the region of Mineiros/GO.